Extreme pools: ecological adaptations in the order Odonata at the inselbergs in the colombian guiana shield (2021)
This study has been purposed to evaluate adaptation strategies in insects of the order Odonata from three main families allocated at the Colombian Guiana shield: Libellulidae, Aeshnidae, and Coenagrionidae. A controlled habitat was used to monitor some previously identified variables to evaluate if there is an environmental effect related to water conditions or quantity that may be responsible for inducing plasticity events, due to stress sensing. All individuals used in this experiment were in the larval stage. Also, we evaluated if there is a behavioral strategy for Odonata larvae to sense different environmental signals that may help them to allocate suitable places to settle. Due to extreme climate changes can make disappear a perfectly suitable place for this type of organism in a short period, it is valuable to know if they have behavioral and/or phenotypic plasticity mechanisms to cope with these demanding conditions. We found relevant information from the Libellulidae family...